A Facile Path to Graphene‐Wrapped Polydopamine‐Entwined Silicon Nanoparticles with High Electrochemical Performance. Issue 2 (12th February 2019) - Liu, Zechen; Huang, Jialiang; Zhao, Xuewen; Huang, Hongyang; Fu, Chengcheng; Li, Zhihui; Cheng, Yonghong; Niu, Chunming; Zhang, Jinying
Abstract: Graphene‐coated silicon nanoparticles with polydopamine buffers have been designed and successfully fabricated as anodes for lithium ion batteries, where the polydopamine was grown on the silicon nanoparticles and then coated with graphene layers. The expansion cavities for silicon nanoparticles during charging and discharging process are provided by the polydopamine buffer layers. The outermost graphene coating layers not only keep the pulverized silicon particles together without disintegration, but also improve the electric conductivity of silicon nanoparticles. Silicon nanoparticles of an industrial product level with different size distributions and oxidation layers were used in this work. High electrochemical performances with specific capacities of 1100 mAh g −1 were achieved by the designed silicon composites with polydopamine and graphene after 550 cycles at a current rate of 200 mA g −1 . Abstract : Graphene‐coated silicon nanoparticles with polydopamine buffers have been designed and successfully fabricated as anodes for lithium ion batteries. A specific capacity around 1100 mAh g −1 has been achieved by the Si@PDA@Gra anodes at a current rate of 200 mA g −1 after 600 cycles. Silicon nanoparticles of an industrial product level could be used without further treatment.